The viper's nest - Lerangis, Peter (New York : Scholastic, 2010)
Amy and Dan travel to a distant land to follow in the footsteps of their most formidable ancestor yet, a military leader who teaches them the art of ancient warfare.
4.5
3-6
Keywords: Families -- History -- Juvenile fiction; Cryptography -- Juvenile fiction; Genealogy -- Juvenile fiction; Family life -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery and detective stories; Family life -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery fiction; Code and cipher stories; Mystery fiction